Spirituality And Its Influence On Job Performance Among Teacher - Suda, John Gimang (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study aims to find out more about spirituality and its influence on job performance among teachers in primary schools. In particular, this study is to examine teachers' perceptions of spiritual concepts, to explore how teachers practice spirituality to improve job performance, to explore spiritual importance in improving job performance, to explore issues and challenges arising in spirituality and job performance and to explore strategies for understand the issues and challenges that arise among teachers. According to Tan Sri Dr Abdullah Muhammad Zin (2017) stated that, spiritual and physical values need to be balanced to avoid being exposed to negative things. This study using qualitative methods. Case studies were used to conduct this study and interview questions were used as instruments to obtain data. Non-probability sampling was used to obtain the most appropriate informant for this study. The findings of this study have revealed the teacher's perception of the concept of spirituality is mostly stated that this spirituality has a relationship with God and about the faith of an individual. Practicing spirituality in daily life has many benefits and positive effects such as being able to give patience in dealing with problems at work. Therefore, practicing this spirituality can have an impact on the work performance of a teacher because a teacher can practice good values. Finally, the findings from this study are important for HR staff to create awareness of the importance of practicing spirituality in the organization so that employees are able to maintain good job performance so that teachers are able to provide highly innovative knowledge to school students.